OS01-12 A computational toolbox supporting the development of Safe and Sustainable by Design chemicals and materials - D. Sarigiannis; F. Nikiforou; A. Karakoltzidis; A. Agalliadou; T. Rydberg; M. Halling; C.L. Battistelli; E. Benfenati; C. Bossa; E. Bouman; É. Bourgé; M. Brouwer-Milovanovic; et al. (Toxicology Letters, 2024)

Correction to: Functional redundant soil fauna and microbial groups and processes were fairly resistant to drought in an agroecosystem - A. Watzinger; J. Prommer; A. Spiridon; W. Kisielinska; R. Hood-Nowotny; S. Leitner; W. Wanek; C. Resch; M. Heiling; E. Murer; H. Formayer; A. Wawra; et al. (Biology and Fertility of Soils, 2023)

Functional redundant soil fauna and microbial groups and processes were fairly resistant to drought in an agroecosystem - A. Watzinger; J. Prommer; A. Spiridon; W. Kisielinska; R. Hood-Nowotny; S. Leitner; W. Wanek; C. Resch; M. Heiling; E. Murer; H. Formayer; A. Wawra; et al. (Biology and Fertility of Soils, 2023)
Climate change scenarios predict more frequent and intense drought periods for 2071 to 2100 for many regions of the world including Austria. Current and predicted lower precipitation scenarios were simulated at a lysimeter station containing a fertile and less fertile agricultural soil for 9 years. 13 C and 15 N-labeled green manure was added in year 8 with the aim to analyze how the predicted precipitation regime affects soil fauna and microbial groups and consequently nitrogen (N) and carbon (C) cycling. Among the investigated mesofauna (collembola and oribatida), the abundance and biodiversity of oribatida was significantly reduced by drought, possibly because they mainly represent K-strategist species with low mobility and consequently the need to adapt to long-term adverse environmental conditions. Microbial community composition and microbial biomass, investigated by phospholipid fatty acid (PLFA) analysis, was indistinguishable between the current and the predicted precipitation scenarios. Nonetheless, soil 13 C-CO 2 emissions and soil water 15 N-NO 3 data revealed decelerated mineralization of green manure under reduced precipitation in the first 2 weeks, but no effects were observed on soil C sequestration or on 13 C incorporation into microbial PLFAs in the following 1.2 years. We found that over a 1-year time period, decomposition was rather driven by plant residue availability than water limitation of microorganisms in the investigated agroecosystem. In contrast, N 2 O emissions were significantly reduced under drought, and green manure derived 15 N accumulated in the soil under drought, which might necessitate the adjustment of future fertilization regimes. The impacts of reduced precipitation and drought were less pronounced in the more fertile agricultural soil, due to its greater buffering capacity in terms of water storage and organic matter and nutrient availability.

Functional Zoning by Site Index to Balance Multiple Objectives for Pine in Southern US Family Forests - Bradley S Resch; Austin Himes; Stephen C Grado; Robert K Grala; Bruno Kanieski da Silva (Journal of Forestry, 2023)
Family forests comprise a significant portion of total forest land area in the southern United States and their owners frequently have multiple, competing objectives. This research evaluated the effectiveness of functional zoning based on site index on forest sizes relevant to family forest owners. A total of fifty family forests were randomly selected from twenty-five counties in the East Texas Pineywoods region. Timber production and northern bobwhite habitat (Colinus virginianus) habitat were used as proxies for competing objectives. It was found that 80% of family forest parcels had sufficient site index heterogeneity to benefit from functional zoning. For forest parcels that could benefit from functional zoning, the benefit in terms of increased land expectation value (LEV) was not found to be dependent on parcel size. On average, this approach increased the LEV $32/ac at a 3% discount rate, $16/ac at 5%, and $9/ac at 7%. This zoning approach supports multiple objectives while minimizing the economic impact of the nonrevenue objectives.

To Waste or Not to Waste: Questioning Potential Health Risks of Micro- and Nanoplastics with a Focus on Their Ingestion and Potential Carcinogenicity - Elisabeth S. Gruber; Vanessa Stadlbauer; Verena Pichler; Katharina Resch-Fauster; Andrea Todorovic; Thomas C. Meisel; Sibylle Trawoeger; Oldamur Hollóczki; Suzanne D. Turner; Wolfgang Wadsak; A. Dick Vethaak; Lukas Kenner (Exposure and Health, 2023)
Micro- and nanoplastics (MNPs) are recognized as emerging contaminants, especially in food, with unknown health significance. MNPs passing through the gastrointestinal tract have been brought in context with disruption of the gut microbiome. Several molecular mechanisms have been described to facilitate tissue uptake of MNPs, which then are involved in local inflammatory and immune responses. Furthermore, MNPs can act as potential transporters (“vectors”) of contaminants and as chemosensitizers for toxic substances (“Trojan Horse effect”). In this review, we summarize current multidisciplinary knowledge of ingested MNPs and their potential adverse health effects. We discuss new insights into analytical and molecular modeling tools to help us better understand the local deposition and uptake of MNPs that might drive carcinogenic signaling. We present bioethical insights to basically re-consider the “culture of consumerism.” Finally, we map out prominent research questions in accordance with the Sustainable Development Goals of the United Nations.

Respiratory syncytial virus associated hospitalizations in preterm infants of 29 to 32 weeks gestational age using a risk score tool for palivizumab prophylaxis - B. Resch; V. S. Bramreiter; S. Kurath-Koller; T. Freidl; B. Urlesberger (European Journal of Clinical Microbiology & Infectious Diseases, 2017)

Respiratory syncytial virus-associated hospitalizations over three consecutive seasons in children with congenital heart disease - B. Resch; S. Kurath-Koller; J. Hahn; W. Raith; M. Köstenberger; A. Gamillscheg (European Journal of Clinical Microbiology & Infectious Diseases, 2016)

Prospective evaluation of clinical scoring systems in infants with bronchiolitis admitted to the intensive care unit - S. Rödl; B. Resch; N. Hofer; I. Marschitz; G. Madler; E. Eber; G. Zobel (European Journal of Clinical Microbiology & Infectious Diseases, 2012)

Ammonia uptake and retention in some cyanobacteria - S. Boussiba; C. M. Resch; J. Gibson (Archives of Microbiology, 1984)